2016
DOI: 10.1016/j.celrep.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the CAPN1 Gene Result in Alterations in Cerebellar Development and Cerebellar Ataxia in Mice and Humans

Abstract: SUMMARY A CAPN1 missense mutation in Parson Russell Terrier dogs is associated with spinocerebellar ataxia. We now report that homozygous CAPN1 null mutations in humans result in cerebellar ataxia and limb spasticity in four independent pedigrees. Calpain-1 knock-out (KO) mice also exhibit a mild form of ataxia due to abnormal cerebellar development, including enhanced neuronal apoptosis, decreased number of cerebellar granule cells, and altered synaptic transmission. Enhanced apoptosis is due to absence of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 46 publications
6
78
1
Order By: Relevance
“…While calpain has been proposed to participate in various disorders related to abnormal protein folding, including Alzheimer's disease (Nixon, 2003), Parkinson's disease (Samantaray et al, 2008), and Huntington's disease (Lee and Kim, 2006), the specific roles of calpain-1 in these disorders have rarely been addressed. The large decrease in the expression of genes and proteins in this pathway fits well with the neuroprotective function of calpain-1 in the brain and the recent findings that humans with calpain-1 deletion exhibit a variety of forms of ataxia/spasticity (Wang et al, 2016a). Decrease in gene and protein expression of the MAP Kinase pathway would also be expected to have widespread consequences considering that this pathway plays critical roles in many brain processes, including synaptic plasticity and cognition (Adams and Sweatt, 2002) as well as stroke (Sun and Nan, 2016) and glioblastoma (Hannen et al, 2017).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…While calpain has been proposed to participate in various disorders related to abnormal protein folding, including Alzheimer's disease (Nixon, 2003), Parkinson's disease (Samantaray et al, 2008), and Huntington's disease (Lee and Kim, 2006), the specific roles of calpain-1 in these disorders have rarely been addressed. The large decrease in the expression of genes and proteins in this pathway fits well with the neuroprotective function of calpain-1 in the brain and the recent findings that humans with calpain-1 deletion exhibit a variety of forms of ataxia/spasticity (Wang et al, 2016a). Decrease in gene and protein expression of the MAP Kinase pathway would also be expected to have widespread consequences considering that this pathway plays critical roles in many brain processes, including synaptic plasticity and cognition (Adams and Sweatt, 2002) as well as stroke (Sun and Nan, 2016) and glioblastoma (Hannen et al, 2017).…”
Section: Discussionsupporting
confidence: 72%
“…Thus, we found that these mice exhibit impairment in several forms of synaptic plasticity in the hippocampus and cerebellum and in various forms of learning and memory Zhu et al, 2017;Heysieattalab et al, 2019). In addition, we also reported that these mice exhibit cerebellar ataxia (Wang et al, 2016a) and are more susceptible to injury in various forms of acute neuronal insults, including traumatic brain injury (Wang et al, 2016b. While these phenotypic differences could be explained by the cellular functions of calpain-1 in the regulation of various pathways, we were interested in exploring potential changes in gene expression that could also account for such differences.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Wang et al recently described four families with autosomal recessive homozygous mutations in CAPN1 resulting in cerebellar ataxia and limb spasticity 2. These patients of Bangladeshi, Italian, Tunisian and French/Spanish descent showed a clinical course of teenage-onset ataxia, gait spasticity and dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…5 CAPN1 encodes a neutral calcium-activated protease known as calpain-1 protein, which is involved in processes of synaptic plasticity, neuronal migration, neuronal maintenance and necrosis, among others. 6 Calpain-1 contains three functional domains, including a protease domain, a C2-like (C2L) Ca 2+ binding domain, and a penta-EF-hand (PEF) Ca 2+ binding domain. 7,8 Notoriously, HSP patients with autosomal recessive inheritance showed higher clinical complexity, especially due to ataxia resulting in ataxiaspasticity spectrum.…”
Section: Introductionmentioning
confidence: 99%